2006
DOI: 10.1136/bjo.2006.105734
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of visual impairment and blindness in Sistan-va-Baluchestan Province, Iran: Zahedan Eye Study

Abstract: The estimated magnitude of visual impairment and blindness was much higher than our expectations. Further investigation of the pattern of vision loss in women and children, particularly as a result of trachoma and amblyopia, is warranted. Implementation of measures to treat curable cases of the study population can improve the situation in the region dramatically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 14 publications
5
30
0
Order By: Relevance
“…For correct comparison with the findings of Tehran and Zahedan studies, 12,13 we reported the results of visual impairment in 40-to 59-year-old participants, similar to Tehran and Zahedan studies. In Tehran and Zahedan studies, visual impairment according to the corrected vision in the age group 40-59 was 1.3% and 9.4%, respectively.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…For correct comparison with the findings of Tehran and Zahedan studies, 12,13 we reported the results of visual impairment in 40-to 59-year-old participants, similar to Tehran and Zahedan studies. In Tehran and Zahedan studies, visual impairment according to the corrected vision in the age group 40-59 was 1.3% and 9.4%, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…[24][25][26][27][28] However, the results of these studies indicate that visual impairment because of uncorrected refractive errors was considerably high in our study, even higher than Tehran and Zahedan studies. 12,13 Considering the fact that the prevalence of the visual impairment in our study was 0.8% and 2.3%, respectively, 1.5% of the participants could prevent from visual impairment by correcting their PVA. The 0.8% of the population who still have visual impairment after correcting refractive errors should either receive surgical intervention or get used to their visual impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of blindness and cataract surgical burden in the study area was very high compared to other regional surveys that have been conducted in Nepal, 3,4 neighboring countries, and elsewhere [5][6][7][8][9][10][11][12][13][14][15][16] (Table 8). The high incidence of cataracts, especially in the Terai area, in Nepal has also been described in the National Blind-ness Survey.…”
Section: Discussionmentioning
confidence: 80%